Food safety knowledge, attitudes and practices among consumers in developing countries: An international survey. (February 2019) - Odeyemi, Olumide A.; Sani, Norrakiah Abdullah; Obadina, Adewale Olusegun; Saba, Courage Kosi Setsoafia; Bamidele, Florence A.; Abughoush, Mahmoud; Asghar, Ali; Dongmo, Fabrice Fabien Dongho; Macer, Darryl; Aberoumand, Ali
Abstract: An international survey among consumers in developing countries from Asia and Africa on food safety knowledge, attitudes and practices (KAP) was carried out using structured questionnaires. Data were collected from 453 consumers comprising 265 from Africa and 188 from Asia. Significant difference (p < 0.05) on food safety knowledge attitude and practice between consumers from Africa and Asia was observed. In Africa, consumers in Cameroon had the least food safety knowledge (73.15 ± 16.43) compared to Ghana (78.19 ± 15.84) and Nigeria (88.16 ± 8.88). Similarly, consumers in Iran had the least food safety knowledge (73.33 ± 19.84) in Asia compared to Malaysia (88.36 ± 11.64) and Pakistan (89.42 ± 9.89). Among the respondents, 89% were aware of food poisoning while 304 (67.1%) consume food kept for long at room temperature. There was significant difference (p < 0.05) in food safety knowledge, attitudes and practices of consumers between Africa and Asia. Overall, respondents from Asia have better food safety knowledge than respondents from Africa. Graphical abstract: Food safety model describing relationship between food safety knowledge, attitude and practices among consumers (Lim et al. 2016). Unlabelled Image Highlights: Food safety knowledge, attitudes and practices (KAP) among consumers in developing countries from Asia and Africa was investigated. There was significant difference (p < 0.05) on food safety knowledge attitude and practice between consumers from Africa and Asia. In Africa, consumers in Cameroon had the least food safety knowledge and Iran in Asia. Consumers from Asia had better food safety knowledge than consumers from Africa.